ChIP: An early activation protocol for isolated blunt chest injury improves outcomes, a retrospective cohort study. Issue 3 (August 2016) - Curtis, Kate; Asha, Stephen E.; Unsworth, Annalise; Lam, Mary; Goldsmith, Helen; Langcake, Mary; Dwyer, Donovan
Abstract: Background: Blunt chest injuries not treated in a timely manner with sufficient analgesia, physiotherapy and respiratory support are associated with increased morbidity and mortality. The aim of the study was to determine the impact of a blunt chest injury early activation protocol (ChIP) on patient and hospital outcomes. Methods: In this pre-post cohort study, the outcomes of patients with blunt chest injury who received ChIP were compared against those who did not. Data including injury severity, patient outcomes, hospital treatments and comorbidites were extracted from medical records. The primary outcome was pneumonia. Secondary outcomes evaluated health service delivery. Logistic and multiple regressions were used to adjust for potential confounding variables. Results: 546 patients were included, 273 in the before-ChIP cohort and 273 in the after-ChIP cohort. The incidence of pneumonia following the introduction of ChIP was reduced by 4.8% (95% CI 0.5–9.2, p = 0.03). In the after-ChIP cohort, more patients received a pain team review (32% vs. 13%, p < 0.001), physiotherapy (93% vs. 86%, p = 0.005) and trauma team review (95% vs. 39%, p < 0.001). There was no difference in length of stay (p = 0.50). Conclusions: ChIP improved the delivery of healthcare services and reduced the rate of pneumonia among patients with isolated chest trauma.